6(x+3)-3x/4-x/2=5x-9

Simple and best practice solution for 6(x+3)-3x/4-x/2=5x-9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(x+3)-3x/4-x/2=5x-9 equation:


x in (-oo:+oo)

6*(x+3)-((3*x)/4)-(x/2) = 5*x-9 // - 5*x-9

6*(x+3)-((3*x)/4)-(x/2)-(5*x)+9 = 0

6*(x+3)+(-3/4)*x-(x/2)-5*x+9 = 0

6*(x+3)+(-3*x)/4-x/2-5*x+9 = 0

(2*4*6*(x+3))/(2*4)+(-3*2*x)/(2*4)+(4*(-x))/(2*4)+(-5*2*4*x)/(2*4)+(2*4*9)/(2*4) = 0

2*4*6*(x+3)-3*2*x+4*(-x)-5*2*4*x+2*4*9 = 0

42*x-4*x-40*x+72+144 = 0

38*x-40*x+72+144 = 0

72-2*x+144 = 0

216-2*x = 0

(216-2*x)/(2*4) = 0

(216-2*x)/(2*4) = 0 // * 2*4

216-2*x = 0

216-2*x = 0 // - 216

-2*x = -216 // : -2

x = -216/(-2)

x = 108

x = 108

See similar equations:

| 3(9-2x)-2x=11 | | 3-n=-6 | | 18/25+1/5 | | (2+6)=-24 | | 7200=800 | | (3x+15)+(2x)=180 | | 5/7p-2/7p+13=6 | | -5x+35=5x+35 | | 2.5p=7.5 | | 4n+6=-122 | | S+3/7=6 | | 9/5/7 | | 4(2b-7)=30-9b | | 1/2(2x^2-4)+10=11 | | 1/5x=54 | | 9/5(7) | | 17p+(-15)p+(-4)p+(-17)+7p(-2)p=b | | -14/-6 | | -3x+2=10 | | 5+4-5+3*8/2=4 | | -9f+72=-18f | | y+3/y=4y | | 5p-10=10 | | 2n+25=106 | | -2/3(x)=9/2 | | 3*n=7 | | 5(2x+6)=-4(-5-3x)+3x | | (x+2)/3=(2x+1)/5 | | -18m+4=8m+4 | | 3+2-15=6 | | 2.5x+15+.95(x-4)=1.2x+2(0.9x-6) | | 0.27-0.03(x+1)=0.03(2-x) |

Equations solver categories